THE ROLE OF PUBLIC RELATIONS IN BUILDING THE CORPORATE IMAGE OF PT WASKITA KARYA LEWAT INSTAGRAM SOCIAL MEDIA - Roys Putra Ramadhan; Arvin Hardian (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
As a popular social media site, Instagram was originally used for social interaction and sharing personal moments. As time goes by its use grows. Apart from being a platform for social interaction, Instagram is now used for various other purposes, including promotion and dissemination of information. This research aims to determine the role of public relations in building the company's image on the social media Instagram @waskita_karya. The theory used is new media theory which is supported by the Instagram concept. The research method used is descriptive qualitative with observation and documentation data collection techniques as well as internet reviews, especially on PT Waskita Karya's Instagram activities. The research results show that PT Waskita Karya has succeeded in optimizing the Instagram feature to provide relevant information related to development in Indonesia. Instagram has become the main platform for publishing content with high interactiveness, global reach and easy accessibility, thereby increasing audience engagement. Relevant information is very useful for creating a relationship with the audience. This research shows that Instagram is effective in supporting PT Waskita Karya in disseminating information.